Nights of Average Nerves: Popular Culture and Me - Haskell, University of Western Australia, Dennis (Asiatic: IIUM Journal of English Language and Literature, 2012)
In this article an Australian poet and critic reflects on his own aims and aesthetics, set against a world that uncritically praises pop culture and largely ignores poetry. The article considers the difference between â€œpopular cultureâ€ and â€œpop culture,â€ and the reasons why poetry has fallen from general view, arguing that it is partly because of the strengths of poetry â€“ which always needs a link to the general community and had it until the advent of Modernism â€“ and partly because of the problems built into contemporary evaluations of poetry. Thus the article shifts between personal values and general issues related to poetry in our time, and advocates a return to a traditional valuing of shared emotions rather than of wilful complexity.